HUBUNGAN KONDISI FISIK LINGKUNGAN RUMAH DENGAN PENYAKIT TB PARU BTA POSITIF DI KELURAHAN LEMPAKE KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Erni Wingki Susanti (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
Tuberculosis (TB) is one of the health problems in the world and an estimated one-third of the world's population has been infected by Mycobacterium tuberculosis. Tuberculosis is closely related to sanitary conditions unsanitary housing. This study aims to determine the relationship of the physical condition of the home environment with pulmonary TB disease in Sub Lempake District of North Samarinda. This type of research is an analytic observational study with cross sectional design. The research sample as many as 70 houses. The sampling technique used cluster random sampling. It is used Chi Square statistical test. The survey results revealed no natural lighting by 41.4% respondents might not qualify. There is a 70% ventilation respondents might not qualify. There amounted to 78.6% of respondents home flooring types that are not eligible, and there was at 48.6% of respondents types of walls of the house are not eligible. No results of the BTA + by 11.4% of respondents (8) the results of examination of sputum positive pulmonary TB. The result of Chi Square test with a significance of ? 0:05 day lighting unknown variables p value 0.007> 0.05; ventilation variables p value 0.047> 0.05; variable types of flooring p value 1.000> 0.05; and variable type wall 0.026 p value of <0.05. Conclusion The correlation between natural lighting, ventilation, and the type of wall with pulmonary TB disease and there is no relationship between the type of floor with pulmonary TB disease.